The Transformation of Gender Stereotypes in Society Due to TikTok as a Social Media Platform - Fransiska L. Tobing, Laura; Lekahena, Maretha (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2025)
As a social media platform, TikTok provided a space for diverse gender expressions, influencing society’s views on gender stereotypes and how they emerged. The purpose of this study was to analyze how TikTok contributed to changing gender stereotypes in society by both dismantling traditional norms and reinforcing existing stereotypes. This study employed a qualitative method to explore gender-related content on TikTok and its impact on public perception. The findings revealed that TikTok served as an effective tool for challenging rigid gender constructs through educational content, self-expression, and alternative narratives. However, the platform also had the potential to reinforce gender stereotypes through trends, algorithms, and the societal expectations it generated. Therefore, depending on how users engaged with it, TikTok played a dual role in shaping gender stereotypes in society. This study aimed to provide deeper insights into the impact of social media on gender construction and serve as a reference for users to respond more critically to TikTok content.